(untitled) (Itinera, 2023)
In this essay, I do not want to focus on performativity as such and understand it as an aesthetic expression; instead, I would like to illustrate how performativity takes on the role consequential to an aesthetic experience. Specifically, I want to highlight how aesthetic experience takes place in the spatial contexts of the city. In this regard, I want to define the aesthetic-practical-sensory relationship of the soma, understood as a paradigm of a living body, that is, a body that moves and acts in space, by declining three historical moments that tell the story. I want to define three historical moments from the early twentieth century to the present through the soma-city relationship: 1) The first moment is inscribed in the emergence of the Baudelairian concept of the flâneur, a symbolic figure who introduces a relationship with the city characterized by a disenchanted gaze and a slow, wandering movement picked up, especially by Walter Benjamin in the Paris Passages; 2) The second moment is that of Situationism, in which Guy Debord introduces the concept of dérive, understood as an approach to the city marked by the experiential and emotional relationship; 3) The third and most recent moment concerns Richard Shusterman’s embodiment of the somaesthetic exercise, in which the Avatar of the Man in Gold, enters into a relationship with the city, aspiring to reconnect urban spheres and not to a pure somaesthetic experience of the city. The last point to be made is that these three historical and aesthetic experience-based moments of the body in the city are marked by the body moving in space. In the case of the flâneur, the body wanders in an unresolved manner without a precise destination; in the case of the drift, the body is propelled by the many sensations and expressions of the city that are expressed through walking (urban Walkscapes); finally, in the case of the Man in Gold, there is a movement totally absorbed in the experience of places.